Factors Influencing Northern Bobwhite Hunting Success on Two South Georgia Plantations - Shane D. Wellendorf; William E. Palmer; D. Clay Sisson (National Quail Symposium Proceedings, 2017)
Success of wild northern bobwhite (Colinus virginianus) management programs on private lands is most often measured by the rate of coveys pointed during the hunting season. Thus, managers of these properties are keenly interested in factors that influence hunting success. We examined how coveys pointed/hour, a measure of hunting success, was influenced by time of hunting season, time of day, weather parameters, and supplemental feeding on 2 intensively-managed plantations over 4 years. There were significant annual differences in the number of coveys pointed/hour among the 4 study years, but hunting success did not vary during the hunting season. Afternoon hunts had consistently higher success rates than morning hunts; however, the effect size was variable from year to year. The selected weather model indicated an interaction between 12-hr barometric pressure change and starting air pressure; hunting success increased with a rapid pressure increase that resulted in a high pressure value at the start of the hunt. A secondary weather model documented a negative relationship between starting air temperature and hunting success. The number of days since supplemental feed was spread had no significant effect on hunting success in 5 of 6 years for the 2 plantations over 3 years. Knowledge of how these variables influence hunting success should improve hunting and provide realistic expectations of hunt success for a given set of circumstances.
Keywords: Colinus virginianus; coveys pointed/hour; Georgia; hunting success; northern bobwhite; season; supplemental feeding; weather